2023
DOI: 10.3390/rs15092420
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of Orchard, Vineyard, and Olive Trees Based on Phenology Metrics Derived from Time Series of Sentinel-2

Abstract: This study aimed to propose an accurate and cost-effective analytical approach for the delineation of fruit trees in orchards, vineyards, and olive groves in Southern France, considering two locations. A classification based on phenology metrics (PM) derived from the Sentinel-2 time series was developed to perform the classification. The PM were computed by fitting a double logistic model on temporal profiles of vegetation indices to delineate orchard and vineyard classes. The generated PM were introduced into… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…However, when it comes to woody crops planted in hedgerow systems, the literature indicates some challenges. Although advances have been made [3,19,20], concerns about the accuracy of Sentinel-2 data in these systems persist. A study by Sozzi et al [21] found a strong correlation between Sentinel-2 and UAV data at both the field and sub-field scales.…”
Section: Resultsmentioning
confidence: 99%
“…However, when it comes to woody crops planted in hedgerow systems, the literature indicates some challenges. Although advances have been made [3,19,20], concerns about the accuracy of Sentinel-2 data in these systems persist. A study by Sozzi et al [21] found a strong correlation between Sentinel-2 and UAV data at both the field and sub-field scales.…”
Section: Resultsmentioning
confidence: 99%
“…Guermazi et al [108] faced difficulties in capturing phenological changes due to local cloudiness, which limited the effectiveness of medium-spatial-resolution imagery in specific orchard types. Abubakar et al [15] reported classification challenges, particularly in young orchards and heterogeneous plots. The interference arising from sparse canopies and age differences in trees underscores the need for improved classification methodologies customized for diverse orchard conditions.…”
Section: Limitations and Future Perspectivesmentioning
confidence: 99%
“…Providing non-destructive methodologies with high spatial, radiometric and temporal resolutions, RS allows the characterization and monitoring of spatiotemporal variability for multidimensional purposes [9][10][11][12][13]. Over the past few decades, RS technology has played a crucial role in the development of new agricultural applications, focusing primarily on monitoring vegetation cover [14][15][16], assessing crop vigor conditions [17][18][19], estimating nutrient and water status [20][21][22], determining crop evapotranspiration (ET c ) [23][24][25], identifying and managing invasive plants [26][27][28], detecting and monitoring pest/diseases [29][30][31] and forecasting crop yields [32][33][34]. The effectiveness of RS applications in agriculture depends on several fundamental factors, including the choice of sensing platform, which can be a satellite, aircraft, unmanned aerial vehicle (UAV) or terrestrial platform; the segment of the electromagnetic spectrum used; the number and range of spectral bands; spatial, temporal and radiometric resolutions; and the energy source (passive or active sensors) [9].…”
Section: Introductionmentioning
confidence: 99%
“…With the arrival of new data at increasingly fine spatial and temporal resolutions such as the Sentinel missions from Copernicus program or Pleiades and SkySat images, it becomes possible to monitor crops systems with more and more accuracy (Jafarzadeh and Attarchi, 2023). Thus (Abubakar et al, 2023) have shown that orchards can be well classified from Sentinel 2 data using deep learning methods. The combination of both, high temporal and spatial resolution of Sentinel 2 images (pixel 10m and time revisit 3-5 days), enables to monitor in-season vegetation phenology through the analysis of time-series.…”
Section: Introductionmentioning
confidence: 99%